Land use/land cover change analysis and its impact on soil properties in the northern part of Gadarif region, Sudan - Biro, Khalid; Pradhan, Biswajeet; Buchroithner, Manfred; Makeschin, Franz (John Wiley & Sons, 2013)
Several decades of intensive dry land farming in the Gadarif region, located in the Eastern part of Sudan, has led to rapid land use/land cover (LULC) changes mainly due to agricultural expansion, government policies and environmental calamities such as drought. In this paper, an attempt has been made to analyse and monitor the LULC changes using multi-temporal Landsat data for the years 1979, 1989 and 1999 and ASTER data for the year 2009. In addition, efforts were made to discuss the impact of LULC changes on the selected soil properties. For this, a post-classification comparison technique was used to detect LULC changes from satellite images. Primarily, three main LULC types were selected to investigate the properties of soil, namely, cultivated land, fallow land and woodland. Moreover, soil samples were also collected at two depths of surface soil from ten sample plots for each of the LULC type. For these soil samples, various soil properties such as texture, bulk density, organic matter, soil pH, electrical conductivity, sodium adsorption ratio, phosphorous and potassium were analysed. The results showed that a significant and extensive change of LULC patterns has occurred in the last three decades in the study area. Further, laboratory tests revealed that soil properties were significantly affected by these LULC changes. The change of the physical and chemical properties of the soil may have attributed to the changes in the LULC resulting in land degradation, which in turn has led to a decline in soil productivity.